Similarity in Neuronal Firing Regimes across Mammalian Species - Mochizuki, Yasuhiro; Onaga, Tomokatsu; Shimazaki, Hideaki; Shimokawa, Takeaki; Tsubo, Yasuhiro; Kimura, Rie; Saiki, Akiko; Sakai, Yutaka; Isomura, Yoshikazu; Fujisawa, Shigeyoshi; Shibata, Ken-Ichi; Hirai, Daichi; et al. (The Journal of neuroscience, 2016)
The architectonic subdivisions of the brain are believed to be functional modules, each processing parts of global functions. Previously, we showed that neurons in different regions operate in different firing regimes in monkeys. It is possible that firing regimes reflect differences in underlying information processing, and consequently the firing regimes in homologous regions across animal species might be similar. We analyzed neuronal spike trains recorded from behaving mice, rats, cats, and monkeys. The firing regularity differed systematically, with differences across regions in one species being greater than the differences in similar areas across species. Neuronal firing was consistently most regular in motor areas, nearly random in visual and prefrontal/medial prefrontal cortical areas, and bursting in the hippocampus in all animals examined. This suggests that firing regularity (or irregularity) plays a key role in neural computation in each functional subdivision, depending on the types of information being carried. By analyzing neuronal spike trains recorded from mice, rats, cats, and monkeys, we found that different brain regions have intrinsically different firing regimes that are more similar in homologous areas across species than across areas in one species. Because different regions in the brain are specialized for different functions, the present finding suggests that the different activity regimes of neurons are important for supporting different functions, so that appropriate neuronal codes can be used for different modalities.